Xanthine Oxidase Inhibitory Activity of Euphorbia peplus L. Phenolics - Kamel, Emadeldin M.; Ahmed, Noha A.; El-Bassuony, Ashraf A.; Hussein, Omnia E.; Alrashdi, Barakat; Ahmed, Sayed A.; Lamsabhi, Al Mokhtar; Arab, Hany H.; Mahmoud, Ayman M. (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Various phenolics show inhibitory activity towards xanthine oxidase (XO), an enzyme that generates reactive oxygen species which cause oxidative damage. Objective: This study investigated the XO inhibitory activity of Euphorbia peplus phenolics. Methods: The dried powdered aerial parts of E. peplus were extracted, fractioned and phenolics were isolated and identified. The XO inhibitory activity of E. peplus extract (EPE) and the isolated phenolics was investigated in vitro and in vivo. Results: Three phenolics were isolated from the ethyl acetate fraction of E. peplus. All isolated compounds and the EPE showed inhibitory activity towards XO in vitro. In hyperuricemic rats, EPE and the isolated phenolics decreased uric acid and XO activity. Molecular docking showed the binding modes of isolated phenolics with XO, depicting significant interactions with the active site amino acid residues. Molecular dynamics simulation trajectories confirmed the interaction of isolated phenolics with XO by forming hydrogen bonds with the active site residues. Also, the root mean square (RMS) deviations of XO and phenolics-XO complexes achieved equilibrium and fluctuated during the 10 ns MD simulations. The radius of gyration and solvent accessible surface area investigations showed that different systems were stabilized at ≈ 2500 ps. The RMS fluctuations profile depicted that the drug binding site exhibited a rigidity behavior during the simulation. Conclusion: In vitro, in vivo and computational investigations showed the XO inhibitory activity of E. peplus phenolics. These phenolics might represent promising candidates for the development of XO inhibitors.
Keywords: phenolics